TSC/mTOR Pathway Mutation Associated Eosinophilic/Oncocytic Renal Neoplasms: A Heterogeneous Group of Tumors with Distinct Morphology, Immunohistochemical Profile, and Similar Genetic Background - Pivovarcikova, Kristyna; Alaghehbandan, Reza; Vanecek, Tomas; Ohashi, Riuko; Pitra, Tomas; Hes, Ondrej (Biomedicines, 2022)
A number of recently described renal tumor entities share an eosinophilic/oncocytic morphology, somewhat solid architectural growth pattern, and tendency to present as low-stage tumors. The vast majority of such tumors follow a non-aggressive clinical behavior. In this review, we discuss the morphological, immunohistochemical, and molecular genetic profiles of the three most recent novel/emerging renal entities associated with TSC/mTOR pathway mutations. These are eosinophilic solid and cystic renal cell carcinoma, eosinophilic vacuolated tumors, and low-grade oncocytic tumors, which belong to a heterogeneous group of renal tumors, demonstrating mostly solid architecture, eosinophilic/oncocytic cytoplasm, and overlapping morphological and immunohistochemical features between renal oncocytoma and chromophobe renal cell carcinoma. All three tumors also share a molecular genetic background with mutations in the mTORC1 pathway (TSC1/TSC2/mTOR/RHEB). Despite the common genetic background, it appears that the tumors with TSC/mTOR mutations represent a diverse group of distinct renal neoplasms.
Keywords: chromophobe; oncocytic; mTOR; EVT; eosinophilic; kidney; LOT; tumor; renal; ESC